Pericoronary adipose tissue and quantitative global non-calcified plaque characteristics from CT angiography do not differ in matched South Asian, East Asian and European-origin Caucasian patients with stable chest pain. Issue 125 (April 2020) - Goeller, Markus; Rahman Ihdayhid, Abdul; Cadet, Sebastien; Lin, Andrew; Adams, Daniel; Thakur, Udit; Yap, Grace; Marwan, Mohamed; Achenbach, Stephan; Dey, Damini; Ko, Brian
Highlights: In blinded core-lab analysis of coronary plaque and RCA PCAT in matched South Asian, East Asian and European-Origin Caucasian patients with stable chest pain: NCP features within the RCA correlated most with the surrounding PCAT attenuation. males showed a significant higher RCA PCAT CT attenuation compared to females. RCA PCAT CT attenuation was comparable. findings might help to define standardized RCA PCAT thresholds for clinical practice. Abstract: Purpose: South Asian (SA) have been observed to have higher cardiovascular mortality rates compared to East Asians (EA) and Caucasians. Pericoronary adipose tissue (PCAT) attenuation around the right coronary artery (RCA) from coronary CT angiography (CTA) has been associated with coronary inflammation and cardiac death. We aimed to investigate i) the relationship between plaque characteristics and PCAT attenuation and ii) to assess gender and ethnic differences in PCAT attenuation using a matched cohort of SA, EA and Caucasians. Method: Three-hundred symptomatic patients who underwent CTA were matched for age, gender, BMI and diabetes (100 in each ethnic group). Semi-automated software was used to quantify the total volumes and burden of non-calcified plaque (NCP), low-density non-calcified plaque (LD-NCP) and calcified plaque (CP) in blinded core-lab analysis. PCAT CT attenuation was measured around the RCA (10–50 mm from RCA ostium), the most standardized model for PCAT analysis. Results: The total volumes and burden of NCP, LD-NCP and CP were comparable in the ethnic groups (each p > 0.05). PCAT attenuation was higher in patients with coronary plaque. PCAT attenuation correlated with the total volumes and burden of NCP, LD-NCP and CP (r>0.17; p < 0.003). Within the RCA this correlation persisted only for NCP features (r>0.39;p < 0.001). Males showed higher PCAT attenuation (p < 0.001). PCAT attenuation was similar between Caucasian, EA and SA (p = 0.32). Conclusions: PCAT CT attenuation correlated most with its surrounded NCP features further highlighting its role as surrogate measure of coronary inflammation. As coronary plaque burden and RCA PCAT attenuation did not differ between ethnic groups, causes of increased cardiac mortality in South Asians needs further investigations.